Structuring Functional Requirements of Control Systems to Facilitate Refinement-based Formalisation - Yeganefard, Sanaz; Butler, Michael (Electronic Communications of the EASST, 2012)
Good requirements structure can greatly facilitate the construction of formal models of systems. This paper describes an approach to requirements structuring for control systems that aims to facilitate refinement-based formalisation. In addition to the well-known monitored and controlled phenomena used to analyse control systems, we also identify commanded phenomenon reflecting the special role that an operator plays in system control. These system phenomena guide the structure of the requirements analysis and documentation as well as the structure of the formal models. We model systems using the Event-B formalism, making use of refinement to support layering of requirements. The structuring provided by the system phenomena and by the refinement layers supports clear traceability and validation between requirements and formal models. As a worked example, we structured the requirements of an automotive lane departure warning system using this approach. We found missing requirements through this process and we evolved the requirement document through domain experts’ feedback and formal modelling.